Never goin' back [videorecording (DVD)] - Frizzell, Augustine; Frizzell, Augustine; Mitchell, Maia; Morrone, Camila; Mooney, Kyle, 1984- (Lions Gate Entertainment, 2018)
Never Goin' Back is a rebellious coming of age tale about two young women who have decided to leave their worries behind and go at life full force with each other. Recent high school drop-outs, they find themselves broke and down on their luck. To make a buck, they become waitresses at a scummy local diner. The work may be crushing their souls, but they're saving the money to go on a beach trip together. However, it's a little difficult to save when parties and drugs are calling their names every night.